IMPLEMENTASI POLA ASUH PROFETIK TERHADAP PEMBENTUKAN KARAKTER ISLAMI ANAK-ANAK - Hamdi Al Hafidz; Zulkarnain Abdurrahman (Fakultas Agama Islam Universitas Muhammadiyah Luwuk, 2023)
The moral degradationthat has occurred in Indonesia has resulted in increasingly rampant crime, including among children who are often found in cases of fights with each other, against their parents, bullying, and other crimes. This happens because of a lack of parenting and character education from parents, family and those closest to them, so that these children form their own character without considering good or bad forthemselvesandtheirenvironment. The reality of orphans who don't have a father or mother makes character a very crucial problem, considering that they don't get complete love and affection like children in general, sometimes they are even far from the characteristic values of Islam. The purpose of this research is to provide an over view of the implementation of prophetic parenting, and to find out the role of orphanages as charitable and social institutions in educating and caring for orphans who need a place to live, substitute parents, propereducation, and fulfillment of other needs. This study uses descriptive qualitative methods through instruments such as interviews, field observations, and documentation. Prophetic parenting style emphasizes exemplary aspects, aspects of habituation, aspects of education and teaching, and social aspects of society